Perbaikan Kualitas dan Dekontaminasi Mikroba Kedelai Edamame Dengan Teknik Ozonated Water - Abi Bakri; Wahyu Suryaningsih; Budi Hariono; Sri Hartatik (Politeknik Negeri Jember, 2018)
Quality, contamination of microorganisms and pesticide residues is a major requirement in edamame export trade. Ozonated water technique is expected to replace the use of chlorine in suppressing microorganism contamination and maintaining quality. Research objectives: a) To determine the effect of various conditions of ozone concentration on quality and contamination of microorganisms on edamame soybeans, b) Comparing the effectiveness of Ozonated Water technique with chlorination, and c) Obtain optimal Ozonated Water method in maintaining quality and eliminating contaminants of microorganisms. The research method used CFRD with 2 Factors ie Factor A of ozone concentration (0, 3, 6 and 9 ppm) and Factor B is Chlorine concentration (0, 100 and 175 ppm) repeated 3 times. The statistical analysis used the Analysis of Variance with the F test and the further difference statistical test of a) the organoleptic quality with Hedonic test includes color, aroma, sweet taste and Hedonic Quality Test for Foreign Odor b) microbiological examination (Total Plate Count). The results are: a) Ozone and chlorine treatment can reduce the total content of edamame microorganisms compared to control, and ozone treatment is more effective in reducing total microbial than chlorine; b) Ozone or Chlorine treatment has no effect on hedonic color and sweetness value in edamame; and c) Ozone treatment may decrease the value of edamame aroma compared with chlorine control and treatment, although in fact Ozone treatment does not contribute to foreign odors or chemical odors to edamame. The conclusion of Ozonated water technique can significantly decrease microorganisms Â contamination and maintain the color quality, sweet taste and donate foreign odors in edamame.Â Keywordsâ€” Ozonated Water, Chlorine , Edamame, Microorganisme